Creative Belgium Awards : the book 2020 - Mortier, Jens, ....-; De bruyn, Dries, ....-; Goldwasser, Jeremie, ....- (Tielt : LannooCampus, 2020)
A dazzling celebration of the brightest ideas by the stars of Belgian advertising. Great brands need great communication to shine, connect and resonate wiht consumers. Creative Belgium honors the most provocative, original and efficient creations in communication design with its highly anticipated annual publication of the greatest in the business. The book 2020 documents the best of contemporary Belgian communication work in advertising, design and digital. It displays the medalists and shortlists of the extraordinary 37th edition of the Creative Belgium Awards. It is a physical testament of an unprecedented virtual ceremony celebrating the stars of the Belgian advertising and graphic design industry.